2016
DOI: 10.1177/0017896916644000
|View full text |Cite
|
Sign up to set email alerts
|

School meals do not have a given place in Swedish school’s quality management

Abstract: Objectives: Sweden is one of three countries worldwide which has a legal requirement to ensure that pupils in compulsory school should be offered free, nutritious school meals. Furthermore, the law states that school meal provision should be included in schools' internal quality management (IQM) system. The objective of this study was to examine to what extent schools in Sweden are following the legal requirement to include school meals in IQM and the relationship between this inclusion and the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…communication of the definition of a pedagogical meal. Including school lunch in the schools’ internal quality management was also associated with taking advantage of teachers’ and school meals staffs’ competence within the area of food and health (Olsson and Waling, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…communication of the definition of a pedagogical meal. Including school lunch in the schools’ internal quality management was also associated with taking advantage of teachers’ and school meals staffs’ competence within the area of food and health (Olsson and Waling, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, actual adherence to policies and guidelines regulating Swedish school lunches varies in practice. A study by Olsson and Waling (2016) showed that 50% of the participating school leaders did not include the school lunch in the IQM. Those who reported that school meals were included in the school's IQM were more likely to see school meals as a constituent part of their educational activities.…”
Section: School Lunch In Swedenmentioning
confidence: 99%
“…At school level, the inclusion of school meals in internal quality management systems, as also required by the new law, is quite low. By 2016 only half of schools surveyed by Olsson and Waling had done so [27]. Of municipalities with local policy documents, only 58% had followed these up within the previous three years [26].…”
Section: Discussionmentioning
confidence: 99%